Size matters: the link between staff size and perceived organizational support in early childhood education. Issue 6 (8th August 2016) - Ho, Dora; Lee, Moosung; Teng, Yue
Abstract : Purpose: This paper examines the relationship between staff size and perceived organizational support (POS) in early childhood education organizations. Design/methodology/approach: A territory-wide questionnaire survey was designed to investigate the perceptions of preschool teachers in Hong Kong on four dimensions of organizational support, namely teacher participation in decision-making, school management support, school performance in organizational support, and organizational negativity in organizational support. In total, 2, 066 teachers from 189 schools were sampled with stratified random sampling. Confirmatory factor analysis and latent mean analysis were employed. Findings: There was a significant relationship between staff size and POS. Specifically, teachers working at small schools in terms of staff size reported significantly higher POS than their counterparts in medium and large schools in aspects including teacher participation in decision-making, school management support, and school performance in POS. Conversely, both medium and large schools had higher scores on organizational negativity. Research limitations/implications: There may exist other factors (e.g., principal leadership), which are not investigated in this study, that influence POS. Future studies are needed to capture a fuller structural relationship among an array of factors that influence POS. Originality/value: Research on staff size and POS has been conducted separately, without one element informing the other. The findings of the present study will stimulate more research on POS and staff size. The study will stimulate thinking about whether larger preschools are more efficient than smaller preschools in terms of scale of economies in a marker-driven, ECE context. Building upon the foundation laid by the study, future studies may explore the interaction between staff size and POS on intended student outcomes in ECE.